Urejanje parcelnih mej v Teksasu - Tacer, Matej (Geodetski vestnik, 2008)
The article describes a view on the land surveying profession in Texas with an emphasis on the boundary determination from the perspective of a Registered Professional Land Surveyor registered in both jurisdictions, Slovenia and Texas, who worked in land surveying in Texas in years 2007 and 2008. The principles of the boundary determination between Slovenia and Texas differ considerably. The main difference roots in (un)involvement of the property owners in the process which brings up numerous questions, i.e. which of the systems is more effective in terms of costs, simplicity and better achievement the overall goal and the mission of the land surveying profession in the society.
Keywords: geodesy; geodezija; parcelne meje; Teksas; United States of America; ureditev; zakonodaja; ZDA